Roles of CDK/Cyclin complexes in transcription and pre-mRNA splicing: Cyclins L and CDK11 at the cross-roads of cell cycle and regulation of gene expression. (November 2020) - Loyer, Pascal; Trembley, Janeen H.
Graphical abstract: Abstract: Cyclin Dependent Kinases (CDKs) represent a large family of serine/threonine protein kinases that become active upon binding to a Cyclin regulatory partner. CDK/cyclin complexes recently identified, as well as "canonical" CDK/Cyclin complexes regulating cell cycle, are implicated in the regulation of gene expression via the phosphorylation of key components of the transcription and pre-mRNA processing machineries. In this review, we summarize the role of CDK/cyclin-dependent phosphorylation in the regulation of transcription and RNA splicing and highlight recent findings that indicate the involvement of CDK11/cyclin L complexes at the cross-roads of cell cycle, transcription and RNA splicing. Finally, we discuss the potential of CDK11 and Cyclins L as therapeutic targets in cancer.